TEACHERS BEHAVIOR TOWARD DIGITAL EDUCATION - Siti Nur Aqila Anuar; Noor Fadhiha Mokhtar; Kalsitinoor Set (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2019)
The education system in Malaysia has increased with the use of computers as a teaching tool. Technological amenities such as Internet technology are created as a successful teaching and learning branch. Terms of Digital education is one of the educational transformation efforts undertaken by Ministry of Education Malaysia (MOE) under the Malaysian Education Development Plan (PPPM) 2013-2025 which focus more on digital and Internet materials at schools and known as a 21st Century Learning (PAK-21). Although the MOE introduced this digital education system for the convenience of teachers, the teacher’s desire to use computers was limited, and there were some constraints faced by teachers in implementing digital classroom teaching. Computer literacy skills became a significant constraint among teachers. Incomplete teachers handle computers; have low confidence in using computers in the school and vice versa (Gilakjani, Mei & Ismail, 2013). This study aims to analyze the intention of Digital Education behavior among Malaysian school teachers and to explore individual skills as an advanced component of the extended Theory of Planned Behavior (TPB). Also, this study aims to examine the role of Attitude, Subjective Normative and Perceived Behavioral as intermediaries on the relationship between individual skills and intentions to use the Internet among school teachers in Malaysia and to develop an extended TPB model including Individual Skills. To achieve this objective, this study examines the behavioural intention of secondary school teachers in Peninsular Malaysia towards this digital education based on the framework of the TPB. A structured questionnaire has been provided to 91 teachers based from table Green (1991) as the samle size for this research and the teachers scome from government secondary schools in Malaysia and to obtain information about the characteristics and performance of their management. A descriptive and inferential analysis was conducted using the Smart PLS 3.0 statistics package. This study provides strong empirical evidence to demonstrate that to increase the use of digital education among teachers in Malaysia there is a need to improve the interest and skills to be exposed to teachers and to use this digital education well and not misused. This can be achieved through the development of a policy and effective government creation and providing greater awareness of digital education programs is easier to use than traditional learning methods